Nauchnaia sektsiia pilotov - Andrei, I. (Russia : Anna Syomkina, 1996)
A film with a David Lynch-type of atmosphere; all characters seem to have something to hide or look as if they are alternating between multiple personalities. All sorts of plots and dangers accumulate during the movie keeping the viewer connected at all times. The sountrack enhances the mysterious circumstances of events. The movie takes place mainly in Moscow subway, but even when scenes are hapenning at the surface the underground feeling and inprint upon the reality is still omnipresent and overpowering.
Duration: 01:53:00